A MIP-enabled stainless-steel hypodermic needle sensor for electrochemical detection of aflatoxin B1. Issue 21 (11th May 2022) - Wood, Marika; Mugo, Samuel M.
Abstract : A robust and reusable molecularly imprinted polymer (MIP)-enabled stainless steel hypodermic needle sensor for sensitive electrochemical detection of aflatoxin B1 (AFB1) in foods and other biological samples. Abstract : Aflatoxin B1 (AFB1) has been identified as one of the most potent naturally occurring carcinogens with high toxicity. The maximum permissible levels of total aflatoxin contamination in food products are limited to 10–15 μg kg −1, as established by the Codex Alimentarius Commission. The widespread occurrence of AFB1 in the food chain identifies them as significant agricultural contaminants of global concern. We herewith demonstrate a molecularly imprinted polymer (MIP)-enabled stainless steel hypodermic needle sensor for sensitive electrochemical detection of AFB1. The stainless-steel hypodermic needle sensor was fabricated using a layer by layer (LbL) film coating comprising multiwalled carbon nanotubes (MWCNTs), cellulose nanocrystals (CNC), and an AFB1 imprinted polyaniline (PANI) biomimetic receptor film. The PANI@MIP/CNC-CNT hypodermic needlesensor showed excellent electrochemical capacitance response (∼10 min) to AFB1 with a linear range of 0–25 nM and a limit of detection (LOD) of 3 nM. Demonstrating good reusability, a single PANI@MIP/CNC-CNT hypodermic needle AFB1 sensor could be reused up to 7 times with a 2.8% relative standard deviation (% RSD) in the sensor's capacitive response. The PANI@MIP/CNC-CNT hypodermic needle sensor was effective in the detection of AFB1 spiked in milk.